2020
DOI: 10.2355/isijinternational.isijint-2019-445
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nano-structure and its Evolution in Heavily Cold-rolled SUS316LN Stainless Steels

Abstract: Evolution of heterogeneous nano-structure in heavily cold-rolled SUS316LN stainless steels was investigated in detail. Transmission electron microscopic observations from the transverse direction (TD) of the 92% rolled specimen revealed the formation of a typical hetero-nano structure composed of ultra-fine lamellar grains embedded with deformation twin domains. The twin domains had prolate ellipsoidal shape elongated parallel to TD. Two types of twin domains with different crystallographical orientations to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…11) In fact, rather good elongation by TWIP is confirmed in SUS316LN stainless steel with heterogeneous nano-structure. 10) From the above results and discussion, it is concluded that UFGed structure can be easily achieved by simple heavy cold-rolling and comparable or more superior mechanical properties than those obtained by SPDs can be attained when grain fragmentation takes place dominantly by dense mechanical twinning. Nevertheless, the experimental results about heterogeneous nano-structure and the properties induced by heavy cold rolling are still not sufficient.…”
Section: Mechanical Propertiesmentioning
confidence: 73%
See 2 more Smart Citations
“…11) In fact, rather good elongation by TWIP is confirmed in SUS316LN stainless steel with heterogeneous nano-structure. 10) From the above results and discussion, it is concluded that UFGed structure can be easily achieved by simple heavy cold-rolling and comparable or more superior mechanical properties than those obtained by SPDs can be attained when grain fragmentation takes place dominantly by dense mechanical twinning. Nevertheless, the experimental results about heterogeneous nano-structure and the properties induced by heavy cold rolling are still not sufficient.…”
Section: Mechanical Propertiesmentioning
confidence: 73%
“…In this way, sharp evolution of ©001ª{110} texture is effectively suppressed. 10,11) It is expected from the above observations of heterogeneous nano-structure, therefore, bendability and ductility would be improved. 12) This will be discussed in detail in the section of 3.3.…”
Section: Microstructure Evolved After Heavy Cold Rollingmentioning
confidence: 93%
See 1 more Smart Citation
“…1, the twin domains surrounded by the shear bands were further embedded in the low-angle lamellae. The twin domains and lamellae were mainly composed of low-energy boundaries of Σ3 coherent twin and low-angle ones, respectively [20], which would provide high restriction to the flow of hydrogen atoms. Therefore, the released hydrogen atoms from the trap sites face high obstacles to preferentially diffuse and accumulate at the stress concentration region (the shear bands located at the tips of twin domains).…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent cold-rolling process led to subdivision and rotation of the twinned region by shear bands, and eventually to the development of HN. 8) Therefore, it can be stated that the deformation twinning that occurred within the initial grains plays the most essential role in the subsequent formation and variant selection of the twin domains. Generally, the deformation twinning is strongly affected by the SFE, 15,16) where deformation twinning becomes easier with decreasing SFE.…”
Section: Discussionmentioning
confidence: 99%